Those for whom the lamp shines : the making of Egyptian ethnic identity in late antiquity - Bantu, Vince L., 1982- (University of California Press, 2023)
"In Those for Whom the Lamp Shines, Vince L. Bantu uses the rich body of anti-Chalcedonian literature to explore how the peoples of Egypt, both inside and outside the Coptic Church, came to understand their identity as Egyptians. Working across a comparative spectrum of traditions and communities in late antiquity, at the intersection of religious and other social forms of identity, Bantu shows that it was the dissenting doctrines of the Coptic Church that played the crucial role in conceptualizing Egypt and being Egyptian. Based on the study of neglected Coptic and Syriac texts, Those for Whom the Lamp Shines offers the only sustained treatment of ethnic and religious self-understanding in Africa's oldest Christian church"--